Space Is the Place : The Lives and Times of Sun Ra - Szwed, John F., 1936- (Book collections on Project MUSE., 2020)
"Sun Ra - a/k/a Herman Poole "Sonny" Blount - was born in Alabama on May 22, 1914. But like Father Divine and Elijah Muhammad, he made a lifelong effort to obscure many of the facts of his early life. After years as a rehearsal pianist for nightclub revues and in blues and swing bands, including Wynonie Harris's and Fletcher Henderson's, Sun Ra set out in the 1950s to find a way to impart his values about the galaxy, Black people, and spiritual matters through the various incarnations of the Intergalactic Arkestra. His repertoire ranging from boogie-woogie, swing, and bebop to free form, fusion, and whatever, Sun Ra was above all a paragon of contradictions: profundity and vaudeville; technical pianistic virtuosity and irony; assiduous attention to arrangements and encouragement of collective improvisation; respect for tradition and celebration of the fresh"--